Specific detection of short-chain alcohols, with the development of an enzyme-coated microcantilever-based biosensor. - MARGARIDO, A. (2022)
This work describes the development and evaluation of a biosensor designed for enzymatic detection of short-chain alcohols, using an X-ray photoelectron spectroscopy (XPS) and atomic force microscopy (AFM). The biorecognition element, alcohol dehydrogenase, was immobilized on self-assembled monolayers deposited on top of silicon nitride microcantilevers. Biosensor assays provided detection of short-chain alcohols and evaluation of the infuence of a biological element immobilization on the analytical performance of the device. The self-assembly process was performed by surface activation using 3-aminopropyltriethoxysilane, followed by glutaraldehyde and biomolecule binding. XPS and AFM were used to verify surface oxidation and reagent binding. The biosensor showed a response time shorter than 1 s, a total renovation of the bioactive layer after 10 min, a sensibility from 0.03 to 1.2 mL/L, and a lifetime of 22 days. Its selectivity was analyzed through exposure to pure and mixed volatile solvents. Sensor sensibility was higher in the presence of short-chain alcohols family (methanol, ethanol, and propanol) ranging from 0.45 to 0.85 kHz and practically null involving other polar or nonpolar solvents. The biosensor showed less susceptibility to humidity and temperature variations, presenting a high-quality factor, a faster response time, selectivity, sensitivity, and durability.